Wdrażanie kontroli zarządczej w jednostkach sektora finansów publicznych: The implementation of management control in the public finance sector units - Sławińska, Joanna (Management and Administration Journal, 2021)
The study was designed to demonstrate the solutions related to the implementation of management control in the public sector. Management control in Polish administration is a tool to support management processes. The control is defined as all measures taken to ensure that the goals and objectives are realized in a manner which is consistent with the law, efficient, cost-effective and timely. The objective of the management is to ensure, in particular, compliance of the unit with the law and internal procedures, efficiency and effectiveness, reliability of the reports, resource protection, observance and promotion of the principles of ethical conduct, efficiency and effectiveness of information flow.The aim of this study is to answer the question: has management control been implemented in Polish public administration in accordance with applicable regulations and standards? This issue is considered on the basis on the criteria of legality and effectiveness. The study presents the model of management control (internal control) used in the United States and most European Union countries, models of financial control and management control in Polish administration, as well as the results of the studies related to the implementation of the above-mentioned control. Bearing in mind that the effectiveness and achievement of results are increasingly important not only in the private sector but also in the public sector, further development and improvement of management control systems in the public administration is expected . The proper functioning of management control is also important to strengthen the accountability of public institutions for their decisions, the implementation of tasks and expenses from public funds.